The return of black box economics: A critique of Keen on effective demand and changes in debt - Severin Reissl (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
In a paper for the Review of Keynesian Economics, Steve Keen recently provided a restatement of his claim that "effective demand equals income plus the change in debt". The aim of the present article is to provide a detailed critique of Keen's argument using an analytical framework pioneered by Wolfgang Stützel which has recently been developed further. Using this framework, it is shown that there is no strictly necessary relationship whatsoever between effective demand and changes in the level of gross debt. Keen's proposed relation is shown not to hold under all circumstances, and it is demonstrated that where it does hold this is due to variations in the "velocity of debt"-variable he introduces. This variable, however, lacks theoretical underpinning. The article also comments on Keen's proposal that trade in financial assets should be included in effective demand, arguing that this undermines the concept of effective demand itself. It is also shown that many weaknesses in Keen's argument stem from a lack of terminological clarity which originates in his interpretation of the works of Hyman Minsky. – – In der Review of Keynesian Economics hat Steve Keen jüngst erneut sein Argument bekräftigt, demzufolge die effektive Nachfrage gleich der Summe aus dem Nationaleinkommen und der Änderung aller Schuldenstände sei. Der vorliegende Artikel verwendet eine ursprünglich von Wolfgang Stützel vorgeschlagene analytische Methode um eine detailierte Kritik von Keens Argument zu entwickeln. Mithilfe dieser Methode wird gezeigt dass kein streng notwendiger Zusammenhang zwischen der effektiven Nachfrage und Änderungen von Schuldenständen besteht. Die von Keen vorgebrachte Relation ist nicht unter allen denkbaren Umständen gültig. In jenen Umständen unter denen sie gültig ist lässt sich dies auf Schwankungen in Keens "velocity of debt"-Variable zurückführen. Diese Variable ist jedoch nicht ausreichend theoretisch untermauert. Der Artikel kommentiert zudem Keens Vorschlag demzufolge Handel mit finanziellen Aktiva (financial assets) zur effektiven Nachfrage hinzugezählt werden solle. Eine Umsetzung dieses Vorschlags würde das Konzept der effektiven Nachfrage selbst untergraben. Es wird auch gezeigt, dass viele der Schwächen in Keens Argumentation auf einen Mangel an terminologischer Klarheit zurückzuführen sind, welcher seinen Ursprung in Keens Interpretation der Werke von Hyman Minsky nimmt.
Keywords: E12; E20; E44; E51; 330; Effective Demand; Endogenous Money; Debt